Effectiveness of applied behavior analysis in the self-help skills and stereotyped behaviors of children with autism spectrum disorder in Isfahan - Movahedzadeh, Bahram; Jamalpour Shah Mansouri, Marziyeh (Social Determinants of Health, 2017)
Background: Applied Behavior Analysis (ABA) is applicable for children and adults with different psychological disorders, developmental disabilities, and learning disabilities. The goal of the present study was to examine the effectiveness of ABA in the increase of self-help skills and reduction of stereotyped behaviors of children with Autism Spectrum Disorder (ASD) in Isfahan, Iran. Methods: this was a quasi-experimental study. The study population included 512 children diagnosed with ASD in Isfahan, Iran during 2015-2016. Using a convenience sampling method, 26 participants were randomly divided into experimental and control groups (13 participants in each group). The study instruments included: the Self-Help Skills Developmental Chart and the Gilliam Autism Rating Scale that were administered at both pretest and posttest. The experimental group received an ABA intervention for 20 sessions (each session: 2 hours) over 3 months. Data analysis was done using IBM SPSS Statistics for Windows, Version 22.0. Results: The results showed that there was a significant difference between autistic children in the experimental and control groups in self-feeding (t=7.01, P=0.01), personal hygiene (t=11.12, P=0.003), mobility impairments and unusual behaviors (t=63.63, P<0.001), verbal and non-verbal behaviors (t=11.58, P<0.001), interaction with people, objects, and situations (t=11.81, P=0.003), and developmental impairments (t=88.28, P<0.001). Conclusion: The ABA appears to be an effective method for increasing self-help skills and reducing stereotypic behaviors in children with ASD. Educational psychologists can use behavioral activation therapy to treat the learning problems of children with ASD.